A Review of Computer Simulation and Other Programs Developed and Used by the Coal Mining Laboratory, Chamber of Mines Research Organization - J. W. Oberholzer (The Southern African Institute of Mining and Metallurgy, 1987)
The use of computers in the South African coal mining industry has increased during the 1980s. Applications at mine level commenced in the financial and personnel areas of payroll systems, mine accounting procedures and staff record keeping. More use is made now on mines of technical programs for purposes such as mine planning and mine survey calculations. The Coal Mining Laboratory of the Chamber of Mines Research Organization has provided, for a number of years, a service to Chamber member collieries in regard to the application of technical computer programs. Programs presently in use for simulating production procedures and conveyor belt transport systems are described. In addition, reference is made to the collection, storage and analysis of data concerning the performance of continuous miners over a period of eight years. More recently a computer program for the simulation of the cutting action of continuous miner cutting drums has been developed. The use of this program to assist with drum design is explained. The fact that many requests to make use of the programs are received from collieries is an indication of their acceptance by industry. Their interest in running the programs themselves on their own desktop computers has led to the need to convert the software for microcomputers.